Long Noncoding RNA RMRP Contributes to Paclitaxel Sensitivity of Ovarian Cancer by Regulating miR-580-3p/MICU1 Signaling. (29th January 2022) - Li, Lingling; Zeng, Saitian; Guo, Liang; Huang, Ping; Xi, Jie; Feng, Jing; Li, Qian; Li, Yanying; Xiao, Xiyun; Yan, Ruixue; Zhang, Jiyan
Abstract : Ovarian cancer is a prevalent female malignancy affecting the health and life of an increasing population of women around the world. Paclitaxel (PTX) resistance is a significant clinical problem in the treatment of ovarian cancer. However, the regulation mechanism of PTX resistance remains unclear. In this investigation, we reported an innovative function of the long noncoding RNA RMRP in promoting PTX resistance and glycolysis of ovarian cancer cells. We observed that RMRP was highly expressed in the ovarian cancer samples, in which the expression of RMRP was elevated in the PTX-resistant patients compared with the PTX-sensitive patients. Meanwhile, RMRP was upregulated in PTX-resistant ovarian cancer cell lines. Functionally, we found that the silencing of RMRP by siRNA significantly enhanced the PTX sensitivity of PTX-resistant ovarian cancer cells, in which the IC50 of PTX was reduced by RMRP depletion. The RMRP knockdown reduced cell viabilities and enhanced cell apoptosis of PTX-resistant ovarian cancer cells. Moreover, we observed that glucose uptake was enhanced in PTX-resistant ovarian cancer cells. The depletion of RMRP decreased glucose uptake, lactate product, and ATP production in PTX-resistant ovarian cancer cells. About the mechanism, we identified that RMRP was able to sponge miR-580-3p to enhance mitochondrial calcium uptake 1 (MICU1) expression in PTX-resistant ovarian cancer cells. MICU1 overexpression and miR-580-3p repression could reverse the RMRP-inhibited proliferation of PTX-resistant ovarian cancer cells in vitro. Thus, we concluded that RMRP contributes to PTX resistance and glycolysis of ovarian cancer by enhancing MICU1 expression through sponging miR-580-3p. Targeting RMRP may serve as a potential therapeutic strategy for the treatment of PTX-resistant ovarian cancer patients.